Feasibility of electroflotation to separate solids and liquid in an activated sludge process - Chung, C. M.; Cho, K. W.; Hong, S. W.; Kim, Y. J.; Chung, T. H. (TAYLOR & FRANCIS LTD, 2009)
In this study, electroflotation (EF) has been applied as a secondary clarification in the activated sludge process to improve the efficiency of the solids-liquid separation, which is essential in maintaining effluent quality. The effects of sludge settleability were examined through a series of batch and semi-continuous experiments. The results of the batch experiments revealed that thickening efficiencies using EF were 2.6 to 9.2 times higher than those with gravity settling (GS). In addition, clarification efficiencies were not significantly influenced by sludge settling properties, as compared with GS as a control. In the semi-continuous EF experiments, the concentrations of solids in the float layer were maintained above 10 g L-1 during flotation, regardless of variations in sludge settleability. Furthermore, the volumetric gas proportion in the float layer increased as the gas to solids (G/S) ratio rose. This allowed the float layer to be more stably suspended against gravity at the top of the reactor. Based on the results obtained from these batch and semi-continuous experiments, an anoxic/oxic (AO) reactor combined with EF clarifier remained in successful continuous operation for four months. In comparison with conventional AO processes using a GS clarifier, enhanced clarification and thickening efficiencies were achieved through the EF-AO system. In addition, higher mixed liquor suspended solids concentrations (averaging 5300 mg L-1) in the bioreactor (EF-AO) were maintained via the return of highly concentrated sludge (averaging 16,400 mg L-1) from the EF clarifier. These findings suggest that EF could be a promising and effective alternative for the solids-liquid separation of poorly settling sludge.